Pengembangan media pembelajaran berbasis web google sites pada materi ikatan ion dan kovalen untuk SMA kelas X - Sitepu, Deri Salsalina Br; Herlinawati, Herlinawati (ARKA INSTITUTE, 2022)
Based on observations that have been made in high school in chemistry learning, it can be seen that during learning, teachers do not use technology enough in their learning, teachers still only use media in the form of textbooks, and give assignments, making learning less interesting for students and sometimes making students not understand the content of the material. learning. This research aims to analyze the development of Google Sites web-based learning media developed for chemistry subjects, and the feasibility of the Google Sites web-based learning media developed. The research and development model for Google Sites web-based learning media uses the ADDIE learning model. This research uses non-test instruments, non-test instruments in the form of validation sheets that meet BSNP standards, namely aspects of appropriateness of content, presentation, language and graphics by a four-category scale validator. The validation feasibility results show that the development of Google Sites web learning media on ionic and covalent bond material is in the valid category. It can be concluded that the Google Sites web-based learning media on ionic and covalent bonds for class X high school is feasible and does not need to be revised.